Pengaruh Pemberian Ekstrak Etanol Daun Sisik Naga (Pyrrosia piloselloides (L.) M. G Price) Terhadap Waktu Pendarahan, Waktu Pembekuan Darah dan Jumlah Trombosit Mencit Putih Jantan - Sri Oktavia; Helmi Arifin; Eddy Duarto (Jurnal Farmasi Higea, 2017)
Research on the effect of ethanol extract of leaf dragon scales (Pyrrosia piloselloides (L.) M. G Price) against clotting time, bleeding time and the number of platelet cells in mice white male. The parameters observed owere the bleeding time, clotting time of blood by the method of the slide and the number of platelet cells by direct calculation method. Animal experiment was divided into 5 groups: negative control group, the dose of 100 mg/kg BW, a dose of 200 mg / kg BW, a dose of 400 mg/kg BW, and by comparison of vitamin K at a dose of 0,026 mg / kg orally. Effects were observed on day 7, 14 and 21. The study showed that ethanol extract leaf dragon scales (Pyrrosia piloselloides (L.) M. G Price) can shorten the bleeding time, shorten the clotting time of blood and increase the number of cells platelet white male mice. A dose of 400 mg/kg BW has been giving maximum effect in shorten bleeding time, shorten the clotting time of blood and can increase the number of platelet cells in mice white male.